Closed Management System Relationship to Students’ Performance: Basis for a Sustainable Classroom Management Program - Jingkun Liu; Rovena I. Dellova (Journal of Elementary and Secondary School, 2024)
Learning styles vary for effective classroom management depending on the appropriate contexts, activities, proper structure, and student empowerment. In China, leadership in schools and universities manifested the closed management requirement during the pandemic, which affected students’ academic performance. This policy causes various effects due to the volume of tasks, mixed feelings, and unstable social interaction. The purpose of the study is to explore the factors of a closed management system and how they affect students’ academic performance towards effective learning and teaching. This study employed a descriptive research design with a quantitative approach using PLS-SEM. There are 341 students’ participants chosen purposefully at Qingdao Vocational College of Aviation Technology. The findings indicate that well-being significantly affects students’ performance. Factors like, fear of being delayed, student participation, family support, and instructor support do not have a substantial direct effect on academic performance. It can be improved by enhancing and facilitating learners’ environmental conditions and promoting well-being. Today, there are limited studies on the impact of the closed management system on students ‘academic performance. Existing studies concentrate on the political and cultural variables that influence the educational system rather than focusing on a particular mechanism. This aspect requires a systematic plan to create a learning environment that prioritizes students’ emotional and academic performance; thus, recommending programs for sustainable classroom management is encouraged.